Heart transplantation: the experience of patients with Chagas disease - Sadala, Maria Lúcia Araújo; Stolf, Noedir Antonio Groppo; Bicudo, Maria Aparecida Viggiani (Revista da Escola de Enfermagem da USP, 2009)
Successful heart transplantation in patients with Chagas disease depends on special care to be provided during all phases of the transplantation process, and requires specific and rigorous follow-up by the health care team. Recipients must be aware of the permanence of the trypanosome in their organisms as well as of the possibility of infection reactivation after transplantation. Therefore, the patient's knowledge regarding this condition and his active participation in his own treatment are of utmost importance. This study aimed at investigating heart transplantation as experienced by patients with Chagas disease, seeking to understand the meanings that they attribute to such an experience. The methodological procedures included: patient selection; interviews; data analysis, indication of the meaning units and individual analysis; search for discourse convergence; and hermeneutic analysis of convergences. From the data analysis, the following themes emerged: the time lived by recipients with Chagas Disease; the conception of heart transplantation presented by patients with Chagas Disease; and care in the course of heart transplantation.